Do púlpito ao baquiço: religião e laços familiares na trama da ocupação do sertão da ressaca - Aguiar, Itamar Pereira de (2007)
This thesis deals with the cultural process and religious traditions existent in Vitória da Conquista, a municipality situated in the Southwest of Bahia, an area identified as Sertão da Ressaca, where Botocudos, Pataxós and Mongoiós Indians lived and interacted mainly with Portuguese, Italian, Spanish and African, mostly Congolese and Angolans. For about two centuries, agriculture and cattle farming were the preponderant activities in the Region and the bull appears as an important element in the society life; perhaps because of this, it dwells in the collective imaginary in the condition of a founding myth. Although the City is inserted in a wider context, a peculiar culture was invented in it, one among the Brazilian ways of living and being. From the second half of the 18th century to the penultimate decade of the 19th century, as evidence has it, only the Catholic religion and the afro-indigenous traditions were present in the Region. From 1890 on, the Kardecist Spiritism and the Baptist Church appeared; in the 1930 s, the presence of caboclos well-organized terreiros de Candomblé is detected. Ever since, other religions appeared. It aims at identifying the presence and diversity of religious traditions in the City and how the so called endogamy-organized traditional families were distributed among the different religions. It focuses on the Baptist Church in its relationship to the others, particularly with the people of saint. It approaches the occupation of the Sertão da Ressaca and the local social, political, economic and cultural organization up to the Proclamation of the Republic. Thence, it divides the City history into three periods: a) from 1900 to 1930; b) 1930 to 1970; c) 1970 to 2005. With a board of Intendants and Mayors, and another with temples from the different religions per neighborhood, it makes up a religious map. The followers of the Baptist Church are at first from traditional families . Then the Church loses its family church characteristics and assumes itself as fundamentalist searching for adepts in popular segments. From 1900 to 1930, schisms between this and the Catholic Church occurred, and followers movement among these religions. In the relations between Baptists and people of saint, there was followers shift between the two religions and the use of magic services from the Afro-Brazilian traditions by Baptists